The risk of medullary thyroid carcinoma in patients with Hirschsprung's disease - Škába, Richard; Dvořáková, Šárka; Václavíková, Eliška; Vlček, Petr; Frantlová, Miroslava; Bendlová, Běla (Pediatric surgery international, 2006)
Hirschsprung's disease (HD) can be associated with the development of neuroendocrine tumours such as medullary thyroid carcinoma (MTC). The RET proto-oncogene is the major gene responsible for both HD and MTC. Mutations in exon 10 (codons 609, 611, 618, 620) were found in patients with co-occurrence of HD and MTC. The aim of the study was to screen the MTC risk in patients with HD. The prospective and retrospective genetic analyses comprised 56 HD patients (41 males, 15 females, aged 0-47). The prospective subgroup of patients consisted of 34 patients (25 boys, 9 girls) operated on between June 2003 and December 2005. The retrospective subgroup comprised 22 patients (16 boys, 6 girls) of 194 patients who were operated on between December 1979 and May 2003, non-systematically chosen preferably for total colonic aganglionosis (TCA). DNAs were isolated from blood and resected segments of aganglionic bowel. The HD patients and nine available family members (2 HD) were tested for RET mutations in exons 10, 11, 13, 14, 15 and 16. Direct double-stranded fluorescent sequencing revealed typical germline heterozygous MTC risk RET mutations in 3/56 (5.4%) female HD patients: Cys609Tyr, Cys620Arg (both exon 10) and Tyr791Phe (exon 13). Two of these patients had TCA and one patient had classical type of HD. One TCA patient developed clinical stage of MTC and underwent total thyroidectomy (TTE). The other two RET positive HD patients (aged 7 and 25 years) are screened for calcitonin level and they are without TTE till now. Two family members (mothers of TCA patients) with detected RET mutation underwent prophylactic TTE with MTC finding. Results showed the benefit of systematic RET mutation screening in HD patients in order to identify the risk of MTC in preclinical stage of the disease in patients with HD and their family members. We recommend to investigate not only exon 10 but also exon 13.
Keywords: zárodečné mutace; nádory štítné žlázy; Humans; Child; kojenec; Adolescent; protoonkogenní proteiny c-ret; Child, Preschool; Thyroid Neoplasms; lidé; medulární karcinom; Carcinoma, Medullary; dítě; Hirschsprungova nemoc; Proto-Oncogene Proteins c-ret; Female; lidé středního věku; Comorbidity; Infant; Male; mladiství; riziko; komorbidita; Adult; předškolní dítě; dospělí; Hirschsprung Disease; Risk; Germ-Line Mutation; Middle Aged; ženské pohlaví; mužské pohlaví